Consequences of Product Quality, Price, and Advertising on Customer Satisfaction Through Electronic AQUA Purchasing Decisions - Santi Wulandari (PT FORMOSA CENDEKIA GLOBAL, 2023)
In order to know and analyze the consequences of product quality, price, and advertising on customer satisfaction through AQUA Electronic purchase decisions. Independent variables of product quality, price, and advertising. The variables are tied up from customer satisfaction, and purchase decisions. Quantitative method, with consumers of AQUA Electronic Official Store on Lazada as the population. The sample was determined using purposive random sampling technique. Primary data was collected from the distribution of questionnaires totaling 135 respondents. Data analysis using regression tests and hypotheses. The quantitative descriptive approach is used to determine the relationship between research variables and surveys. Interval scales are used to make it easier for questionnaires to be filled out. The hypothesis was tested by linear regression to see the consequences of variable product quality, price, and advertising on customer satisfaction through purchasing decisions in AQUA Elektronik